2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.253-483
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an In Silico Cardiac Cell Model for Proarrhythmia Risk Assessment

Abstract: Drug-induced Torsade-de-Pointes (TdP) has been responsible for the withdrawal of many drugs from the market and is therefore of major concern to global regulatory agencies and the pharmaceutical industry. The Comprehensive in vitro Proarrhythmia Assay (CiPA) was proposed to improve prediction of TdP risk, using in silico models and in vitro multi-channel pharmacology data as integral parts of this initiative. Previously, we reported that combining dynamic interactions between drugs and the rapid delayed rectif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…To our knowledge, however, this is the first application of such a simulation in biomedicine. We recognize that studies using a single-cell model of electrophysiology have reported excellent risk prediction (Mirams et al, 2011;Dutta et al, 2017), but comparisons with the clinical data ( Figure 2), evaluation of various ECG indices ( Figure 6) and examinations of heart morphology (Supporting Information Figure S2.32) can be made only with the multiscale simulation. We are aware of those studies examining the ECG changes using one-dimensional models in which transmural distribution of different cell speciesthat is, endocardial, mid-myocardial and epicardial cellsare reproduced (Bottino et al, 2006;Suzuki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, however, this is the first application of such a simulation in biomedicine. We recognize that studies using a single-cell model of electrophysiology have reported excellent risk prediction (Mirams et al, 2011;Dutta et al, 2017), but comparisons with the clinical data ( Figure 2), evaluation of various ECG indices ( Figure 6) and examinations of heart morphology (Supporting Information Figure S2.32) can be made only with the multiscale simulation. We are aware of those studies examining the ECG changes using one-dimensional models in which transmural distribution of different cell speciesthat is, endocardial, mid-myocardial and epicardial cellsare reproduced (Bottino et al, 2006;Suzuki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because of limited computational resources, we simulated only five beats for each case. Studies using a single-cell model repeated the simulation for 1000 cycles to reach steady state (Dutta et al, 2017). Also, using a ventricular model, Sadriegh et al showed that the convergence of T-wave morphology requires more than 100 beats (Sadrieh et al, 2014).…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional references are provided. [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]…”
Section: The Comprehensive In Vitro Proarrhythmia Assaymentioning
confidence: 99%